Down-Regulation of miR-34a-5p Potentiates Protective Effect of Adipose-Derived Mesenchymal Stem Cells Against Ischemic Myocardial Infarction by Stimulating the Expression of C1q/Tumor Necrosis Factor-Related Protein-9 - Weng, Chi-Feng; Wu, Ching-Feng; Kao, Shao-Hsuan; Chen, Jeen-Chen; Lin, Hui-Han (Frontiers in Physiology, 2019)
Adipose-derived stem cells (ADSCs) have shown great promise for the treatment of myocardial infarction (MI), although their potential therapeutic mechanism remains poorly understood. Growing evidence has implicated microRNAs (miRNAs or miRs) in the biological processes whereby ADSCs could ameliorate cardiovascular disease. In this study, we explored the contribution of miR-34a-5p down-regulation to the protective actions of ADSCs against MI. We initially identified the interaction between miR-34a-5p and C1q/tumor necrosis factor-related protein-9 (CTRP9) through in silico analysis. We next tested the effects of miR-34a-5p and CTRP9 on the expression of extracellular signal-regulated kinase 1 (ERK1), matrix metalloproteinase-9 (MMP-9), nuclear factor (erythroid-derived 2)-like 2 (NRF2), and antioxidant proteins [manganese superoxide dismutase (MnSOD), and heme oxygenase-1 (HO-1)] through gain- and loss-of-function tests. In other experiments, we assessed the proliferation, migration, and apoptosis of ADSCs using the EdU assay, scratch test, Transwell assay, and flow cytometry. Finally, we studied whether miR-34a-5p/CTRP9 axis could modulate the protective effect of ADSCs against MI during stem cell transplantation in MI mouse models. miR-34a-5p could target and down-regulate CTRP9 in cardiomyocytes. Down-regulated miR-34a-5p increased the expression of ERK1, MMP-9, NRF2, MnSOD, and HO-1, whereas down-regulation of miR-34a-5p or up-regulation of CTRP9 in vitro promoted ADSC proliferation and migration and inhibited ADSC apoptosis. Moreover, miR-34a-5p down-regulation or CTRP9 up-regulation promoted the protective role of ADSCs against MI damage in vivo. Thus, inhibition of miR-34a-5p may facilitate ADSC’s protective function against MI damage by stimulating the expression of CTRP9.